Synthesis and characterization of bile acid‐based polymeric micelle as a drug carrier for doxorubicin. (23rd August 2021) - Altinkok, Cagatay; Acik, Gokhan; Karabulut, Huseyin Riza Ferhat; Ciftci, Mustafa; Tasdelen, Mehmet Atilla; Dag, Aydan
Abstract: In the present study, a polymeric micelle based on amphiphilic block copolymer, namely poly(methacrylated methyl lithocholate)‐ block ‐poly(oligoethylene glycol methacrylate) (PMML‐ b ‐POEGMA) bearing bile acid moiety is prepared via sequential photo‐initiated free radical polymerizations, and its drug carrying capacity is investigated using doxorubicin hydrochloride (DOX) as a model drug. For this purpose, two‐step procedure is applied in the presence of phenylbis (2, 4, 6‐trimethylbenzoyl)phosphine oxide (BAPO) as bifunctional photo initiator. Based on spectroscopic and chromatographic analyses, the desired amphiphilic block copolymer (PMML‐ b ‐POEGMA) is successfully synthesized by wavelength‐selective free radical photopolymerization under mild conditions. Finally, the DOX drug is loaded into the PMML‐ b ‐POEGMA micelles and then drug release behavior is investigated at two different pH (5.5 and 7.4) values. It is concluded from the results that PMML‐ b ‐POEGMA micelles may be used as an efficient nanocarrier to deliver conventional anti‐cancer drugs for combination chemotherapy.